Analisis Elemen Desain Pada Metafora Arwana Merah Dalam Busana Bergaya Sexy Dramatic - Yeni, Ni Putu Ryani Puspa (Besaung : Jurnal Seni Desain dan Budaya, 2023)
Red Dragon is a fashion collection inspired by the red Arowana fish and embodied by the metaphor of the red Arowana fish in a sexy dramatic style piece of clothing. Every piece of clothing has several elements that form a single unit called design elements or design components. Design elements have an important role in a work of art, especially design elements and principles that can be seen from fashion design, detail, and material selection so that the value of beauty is formed in the clothes used. Red Dragon's fashion works are composed of design elements consisting of design elements and principles. The design elements in Red Dragon's fashion work consist of points, lines, planes, shapes, spaces, textures, and colors. In addition to design elements, Red Dragon's fashion works also have design principles that include unity, rhythm, balance, proportion, and center of interest. Design elements and principles are arranged in a fashion work systematically so as to form an order that has beauty.